HUBUNGAN ANTARA KARAKTERISTIK SOSIAL EKONOMI PETANI DENGAN TINGKAT ADOPSI TEKNOLOGI PHT PASCA SLPHT KAKAO DI DESA JATIREJO KECAMATAN GIRIMARTO, KABUPATEN WONOGIRI - ATIK NUR FARIDA; S. SUSWADI (JURNAL ILMIAH AGRINECA, 2017)
Abstract:               This study aims to determine the level of farmers 'adoption of the IPM post IPM FFS cocoa Wonogiri, knowing the socio-economic characteristics of farmers IPM FFS in Wonogiri, determine the relationship between socio-economic characteristics at the level of farmers' adoption of the IPM post IPM FFS cocoa Wonogiri. The choice of location is done deliberately or purposive Jatirejo Village, District Girimarto, Wonogiri, and the basic method used in this research is descriptive analytic method. Based on the analysis and discussion it can be concluded that the first level of farmers' adoption of the post IPM IPM FFS Jatirejo cocoa in the village, at the high category The third relationship between socio-economic characteristics at the level of farmers' adoption of the IPM post IPM FFS cocoa Jatirejo Village is a factor of age, non-formal education, income, and the number of tangungan show the relationship is not real, while the factor of formal education, the experience of farmers, and social characteristics the economy is showing real relationship.